Central visual field impairment during and following cystoid macular oedema. Issue 1 (25th June 2007) - Kiss, C G; Barisani-Asenbauer, T; Simader, C; Maca, S; Schmidt-Erfurth, U
Abstract : Aim: To determine differential light threshold values obtained with the Micro Perimeter 1 (MP1) in uveitis patients suffering from cystoid macular oedema (CMO) and to compare these measures to retinal thickness. Methods: Static threshold perimetry was performed with the MP1 Microperimeter in 27 eyes of 21 patients with a history of chronically recurring CMO. Active CMO was confirmed in 19 eyes. Eight eyes with a history of recurrent CMO were found to have normal foveal contours in optical coherence tomography (OCT). Differential light threshold values (MP1) were compared with the corresponding retinal thickness measures (OCT). Results: Mean differential threshold values within the central two degrees of the stimulation pattern were reduced compared with normal values and ranged from 5.8 to 9.5 dB in CMO eyes and from 9.3 to 12.9 dB in eyes with a normal foveal contour but a history of previous CMO. The corresponding mean retinal thickness ranged from 390 (SD 90) to 389 (88) μm (at 0° and 1°, respectively) for active CMO and from 199 (36) to 211 (33) μm in eyes with normal fovea following CMO resolution. Statistical correlations between mean differential sensitivity threshold and retinal thickness were only weak and showed no association. Conclusions: Active CMO causes a marked reduction in central retinal sensitivity. In addition, following the resolution of the CMO, a substantial impairment of central retinal sensitivity remains. Morphology in terms of retinal thickness in OCT does not correlate with visual function in terms of retinal sensitivity in these patients.